Understanding Knowledge, Attitude, Behavior, and Dynamic Transmission of Dengue Haemorrhagic Fever in South Tangerang and Bekasi City - Nurusysyarifah Aliyyah; Haryoto Kusnoputranto; Margareta Maria Sintorini; Suyud Warno Utomo; Okky Assetya Pratiwi; Epi Ria Kristina Sinaga (Universitas Airlangga, 2026)
Introduction: Dengue Hemorrhagic Fever (DHF) is a viral infection prevalent in tropical and subtropical climates worldwide, primarily in urban and semi-urban areas. The World Health Organization has documented that Indonesia ranks among the nations with the highest incidence of DHF in Southeast Asia and is classified as one of the most dengue-endemic territories globally. Climate factors leading to an increase in the spread of the dengue epidemic, including the changing distribution of the responsible vectors to DHF. This study aims to encourages urban resident’s knowledge, attitudes, and behavior towards DHF prevention and to investigates the dynamic transmission of DHF affected by climate factors in South Tangerang and Bekasi City. Methods: A cross-sectional study design was used, along with a chi-square test, modeling, simulation, and intervention. Interviews with respondents include knowledge, attitudes, and community behavior. Climate factor measurements include rainfall, temperature, humidity, and CO2 level in the ambient environment. Results and Discussion: The results show that urban resident’s knowledge, attitudes, and behavior regarding the DHF prevention were in good categories. Climate variability patterns affect the dynamic transmission of DHF in South Tangerang and Bekasi City. Conclusion: The government and community need to play a vital role in increasing residents' knowledge, attitudes, and behavior regarding dengue fever through information media, and also implement proper preventive measures.